Diagnosis of the agri-food value chains in the Republic of Moldova - Alexandru Stratan; Victor Moroz; Eugenia Lucasenco (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
The main aim of the paper is to present the state of the agro-food value chain in the Republic of Moldova in conditions of incomplete information and uncertainty. In order to accomplish this general scope, the methodological approaches were adjusted to the available scarce data and existing research resources. Three important outputs are foreseen as a result of the investigation: description of the current situation of the components of agri-food value chains and interaction among them; the rapid analysis of the main dimensions of the chain; identification of constraints and development opportunities. Performance of the agro-food value chains in the Republic of Moldova is affected by high energy costs, unstable sources of inputs supply, restricted access to end-markets. It is also necessary to improve the investment climate in order to modernize the agri-food chains.
Keywords: 330; agri-food value chains; added value; vertical integration